Personal characteristics, gardening engagement, and the value of local garden: a social and economic perspective - Jeong, Miae; Park, Jiwon; Lee, Haemin; Lee, Jooyeong (Frontiers in Sustainable Cities, 2025)
IntroductionIn South Korea, government-led garden development has shifted gardens from private spaces to public domains.MethodsThis study evaluates the economic value of gardens’ social functions by analyzing the willingness-to-pay (WTP) and usage patterns of 759 visitors across seven local gardens.ResultsOn average, visitors spent 77 min traveling, with women aged 50 + reporting high stability and healing. Middle- and low-income groups (incomes below 4 million KRW) had a WTP rate of 68.1%, and garden creation experience raised WTP to 70.5%. The estimated WTP was 5,932 KRW per person per day.DiscussionThese findings provide key evidence for policies addressing regional depopulation and social isolation.